2003
DOI: 10.1038/nature01533
|View full text |Cite
|
Sign up to set email alerts
|

The exocyst complex is required for targeting of Glut4 to the plasma membrane by insulin

Abstract: Insulin stimulates glucose transport by promoting exocytosis of the glucose transporter Glut4 (refs 1, 2). The dynamic processes involved in the trafficking of Glut4-containing vesicles, and in their targeting, docking and fusion at the plasma membrane, as well as the signalling processes that govern these events, are not well understood. We recently described tyrosine-phosphorylation events restricted to subdomains of the plasma membrane that result in activation of the G protein TC10 (refs 3, 4). Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
380
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(396 citation statements)
references
References 31 publications
14
380
1
1
Order By: Relevance
“…Roles for the exocyst in insulin secretion and septins in glucosestimulated growth-hormone release have been reported previously (Inoue et al, 2003;Beites et al, 1999), and the data presented here further indicate that IQGAP1 associates with these protein complexes to regulate their effects on secretion in cooperation with CDC42-GTPase (Figs 1 and 9). This agrees with the finding that stable expression of CDC42, while enhancing mastoparanactivated CDC42 insulin secretion, inhibited glucose-stimulated secretion (Fig.…”
Section: Involvement Of Iqgap1 In Physiological Secretionsupporting
confidence: 80%
See 1 more Smart Citation
“…Roles for the exocyst in insulin secretion and septins in glucosestimulated growth-hormone release have been reported previously (Inoue et al, 2003;Beites et al, 1999), and the data presented here further indicate that IQGAP1 associates with these protein complexes to regulate their effects on secretion in cooperation with CDC42-GTPase (Figs 1 and 9). This agrees with the finding that stable expression of CDC42, while enhancing mastoparanactivated CDC42 insulin secretion, inhibited glucose-stimulated secretion (Fig.…”
Section: Involvement Of Iqgap1 In Physiological Secretionsupporting
confidence: 80%
“…Whereas the yeast exocyst communicates with several members of the Rho subfamily of small GTPases, including Cdc42p (Lipschutz and Mostov, 2002;Novick and Guo, 2002), in mammals, only RAL (RALA) and TC10 (RHOQ) GTPases have been shown to bind the exocyst (Inoue et al, 2003), and no link has been reported with CDC42. Recently, genetic and biochemical evidence have shown that both yeast and mammalian exocysts communicate with the ER-translocon via an interaction with the Sec61␤ subunit (Lipschutz et al, 2003;Toikkanen et al, 2003), suggesting a role in protein synthesis/translocation events.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sec8 associates with the PDZ domain of SAP97 a MAGUK (membrane-associated guanylate kinase) family member that is recruited along with Sec8 [33]. Interestingly, expression of a dominant-interfering Exo70 protein or siRNA-mediated knockdowns did not prevent GLUT4 vesicle trafficking to the plasma membrane but did inhibit GLUT4 plasma membrane fusion whereas over expression of Sec6 and Sec8 enhanced GLUT4 translocation to the plasma membrane [33,35]. Although these data indicate that the Exocyst complex plays an important role in the insulin-regulated plasma membrane docking/tethering of GLUT4 vesicles, it is well established the physiologic minimal fusion machinery is dependent upon the assembly of the SNARE complex [36][37][38] SNARE proteins can be generally classified as v-SNAREs (or R-SNAREs) that possess a single coil-coiled domain and a transmembrane domain that are localized in vesicle compartment [39][40][41][42].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 99%
“…In this case, Cbl phosphorylation has been suggested to provide a pathway for the activation of a small GTP binding protein TC10 that is localized to lipid raft microdomains [86]. Using a constitutively active TC10 protein as bait, several interacting partners were identified including Exo70, as previously described, and CIP4/2 [35,87]. CIP4/2 (Cdc42-interacting protein 4/2) is a modular domain protein containing an FCH domain, which has been recently recognized as part of a larger structural domain called EFC or F-BAR.…”
Section: Insulin Signaling Leading To Glut4 Translocationmentioning
confidence: 99%
“…As shown in Figure 4 and Table 1, the interaction between exo70-1 and 5% PI(4,5)P 2 was almost abolished, indicating that K632 and K635 are critical residues for the binding of Exo70 to PI(4,5)P 2 . Interestingly, the binding of exo70-1 for PS was only partially affected, suggesting that these two residues confer certain degree of specificity for PI(4,5)P 2 .It was previously shown that Exo70 interacts with the constitutively activated form of TC10 (Q67L; Inoue et al, 2003). We then tested whether mutations in exo70-1 affect this interaction.…”
mentioning
confidence: 99%